Impact of Multidrug Resistance Protein-4 Inhibitors on Modulating Platelet Function and High on-Aspirin Treatment Platelet Reactivity - Alemanno, Laura; Massimi, Isabella; Klaus, Vanessa; Guarino, Maria Luisa; Maltese, Teresa; Frati, Luigi; Angiolillo, Dominick J.; Pulcinelli, Fabio M. (Thrombosis and Haemostasis, 2018)
Platelet multidrug resistance protein 4 (MRP4) plays a modulating role on platelet activation. Platelet function and thrombus formation are impaired in MRP4 knockout mice models, and, among aspirin-treated patients, high on-aspirin residual platelet reactivity (HARPR) positively correlates with MRP4 levels. To better understand the effects of MRP4 on platelet function, the aim of this investigation was to assess the impact of cilostazol-induced inhibition of MRP4-mediated transport and assess aspirin-induced antiplatelet effects and rates of HARPR in human subjects.Cilostazol-dependent inhibition of MRP4-mediated transport was assessed with the release of the fluorescent adduct bimane-glutathione and aspirin entrapment. Effect of Cilostazol on cAMP inhibition was evaluated by vasodilator-stimulated phosphoprotein (VASP). Platelet function was studied by collagen and TRAP-6-induced platelet aggregation and secretion.Cilostazol reduced the release of bimane-glutathione and enhanced aspirin entrapment demonstrating an inhibitory effect on MRP4 in platelets. VASP phosphorylation was absent until 10 seconds after addition of cilostazol, and becomes evident after 30 seconds. An inhibitory effect on platelet aggregation and secretion was found in activated platelets, with threshold concentration of agonists, 10 seconds after addition of cilostazol, supporting a role of MRP4 on platelet function that is cAMP independent. Cilostazol effects were also shown in aspirin-treated platelets. A reduction of platelet aggregation and secretion were observed in aspirin-treated patients with HARPR.This study supports the role of MRP4 on modulating platelet function which occurs through cAMP-independent mechanisms. Moreover, inhibition of MRP4 induced by cilostazol enhances aspirin-induced antiplatelet effects and reduces HARPR.
Keywords: platelet function; multidrug resistance protein-4; aspirin